THE IMPACT OF CREATIVITY, INNOVATION AND LEARNING BUSINESS WITH THE PROBLEMS OF BEAUTY'S FRIENDLESS COSMETICS COMPANY IN MAMUJU CITY - Afifah Nurian Aryanti; Marhawati Najib; Agus Syam; Muhammad Rakib; Muhammad Jufri (Adisam Publisher, 2025)
This research aims to find out the impact of creativity, innovation and entrepreneurial knowledge on business success. The method used in this study is quantitative, aimed at explaining the relationship between variables, but the conclusions drawn from the results of the study cannot be simplified and concluded unilaterally but must go through several stages of testing. Data collection using primary data with the technique of division of questionnaires to respondents. Sampling technique used is the method of sampling a saturated sample of 50 respondents Data analysis using SPSS V.24.00 for windows. The results of the research concluded that (1) creativity has a significant positive influence on the success of the business at the Beauty Friend Cosmetic Shop in Mamuju City. (2) Innovation has significant positive impact on the successful business at Beauty Friend cosmetic shop in Mumuju city. (3) Knowledge of entrepreneurship has significantly positive influences on the business success of Beauty Friend Kosmetic Store in Memuju. (4) Creativity, innovation and entrepreneurial knowledge simultaneously have an impact on business success at Beautyfriend Cosmetics store in Mmuju City.